2014
DOI: 10.4172/2157-7110.1000354
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Herbal Products during Breastfeeding: A Study from a Public Italian Hospital

Abstract: Background: The use of herbal products is steadily increasing worldwide, especially by women, also during pregnancy and breastfeeding, even if safety data are lacking. Aim of this study was to estimate the prevalence of use and the attitude toward herbal remedies among women during breastfeeding, by an interview-based survey. Methods: Participants were interviewed after receiving the informed consent, by a structured and validated questionnaire. Results: Two hundred forty-four breastfeeding women completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
1
18
1
1
Order By: Relevance
“…In this study, it was found that over 50% of the women in Macau used at least 1 T/CM during breastfeeding. The findings about the common use of T/CM during breastfeeding are in consistence with what have been previously reported in other countries: 16% in the USA [12], 59.9% in Australia [7], 97% in Italy [16], and 45% in China [8]. While the lower prevalence of T/CM use in the USA may be a true representation, it may also be associated with differences in study design.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, it was found that over 50% of the women in Macau used at least 1 T/CM during breastfeeding. The findings about the common use of T/CM during breastfeeding are in consistence with what have been previously reported in other countries: 16% in the USA [12], 59.9% in Australia [7], 97% in Italy [16], and 45% in China [8]. While the lower prevalence of T/CM use in the USA may be a true representation, it may also be associated with differences in study design.…”
Section: Discussionsupporting
confidence: 86%
“…This opens a potential opportunity to be a reliable source of T/CM information. Clearly, standardized peer reviewed information and guidelines for breastfeeding women and those that care for them are needed [16,62,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While commonly used to treat chronic medications, there is increasing evidence for the use of maternal TCM (particularly herbal medicine) during pregnancy, childbirth and postpartum, including during breastfeeding (117)(118)(119)(120)(121). Studies regarding the effects of TCM use on breast milk components, the breast milk microbiota, and the gut microbiota are lacking.…”
Section: The Effects Of Urbanization On Medication Usementioning
confidence: 99%
“…Bitkisel ürünler infertilite, amenore, doğum kontrolü, gebelik, doğum ve doğum sonrası emzirme döneminde kullanılmaktadır (13) . Avustralya, İtalya ve Taiwan'dan yapılan çalışmalarda, özellikle emzirme döneminde kullanılan bitkisel ürünler ile ilgili çalışmalar bulunmaktadır (14)(15)(16) .…”
Section: Gereç Ve Yöntemunclassified